ATXN1 repeat expansions confer risk for amyotrophic lateral sclerosis and contribute to TDP-43 mislocalization. Issue 2 (19th May 2020) - Tazelaar, Gijs H P; Boeynaems, Steven; De Decker, Mathias; van Vugt, Joke J F A; Kool, Lindy; Goedee, H Stephan; McLaughlin, Russell L; Sproviero, William; Iacoangeli, Alfredo; Moisse, Matthieu; Jacquemyn, Maarten; Daelemans, Dirk; et al.
Abstract: Increasingly, repeat expansions are being identified as part of the complex genetic architecture of amyotrophic lateral sclerosis. To date, several repeat expansions have been genetically associated with the disease: intronic repeat expansions in C9orf72, polyglutamine expansions in ATXN2 and polyalanine expansions in NIPA1 . Together with previously published data, the identification of an amyotrophic lateral sclerosis patient with a family history of spinocerebellar ataxia type 1, caused by polyglutamine expansions in ATXN1, suggested a similar disease association for the repeat expansion in ATXN1 . We, therefore, performed a large-scale international study in 11 700 individuals, in which we showed a significant association between intermediate ATXN1 repeat expansions and amyotrophic lateral sclerosis ( P = 3.33 × 10 −7 ). Subsequent functional experiments have shown that ATXN1 reduces the nucleocytoplasmic ratio of TDP-43 and enhances amyotrophic lateral sclerosis phenotypes in Drosophila, further emphasizing the role of polyglutamine repeat expansions in the pathophysiology of amyotrophic lateral sclerosis. Abstract : Repeat expansions are being identified as part of the complex genetic architecture of amyotrophic lateral sclerosis. This study shows a significant association between intermediate ATXN1 repeat expansions and amyotrophic lateral sclerosis, possibly via mislocalization of TDP-43, further emphasizing the role of polyglutamine expansions in the pathophysiology of amyotrophic lateral sclerosis. Graphical Abstract: